The Effect of Proteus Application on Self-Learning Ability in Electronic Engineering Students: A Literature Review - Fadhila, Aisyah Nur; Sukma, Azzahra Diana; Nastiti, Riri; Kusumawardani, Cycylia; Mahera, Nasywa Allena Deva (Jurnal Inovasi Pembelajaran Karakter, 2024)
An individual's ability to retain and develop knowledge, skills, and comprehension without reservation may be referred to as autonomous learning capacity. Cognitive abilities, approaches, and behaviours that allow people to need movement in their claim learning handle are examples of free learning skills. Additionally, the ability to memorize independently influences the 21st-century skills that students need to possess, which include creative thinking, problem-solving, communication, and teamwork. However, it is commonly seen that understudies of hardware design still have weak free-learning abilities. The instructor still plays a huge role and serves as a sort of learning resource for students as they work through problems. The primary reason is believed to be that learning materials are less effective at promoting free education, making students less important than teachers. This study aims to examine how the Proteus program affects hardware design understudies' ability to learn on their own. The question regarding the approach taken could be a survey on story-writing. As test-related questions, up to 20 articles from international diaries were used. According to research findings, the Proteus application helps students in Mechanical Hardware Building increase their capacity for independent learning. Typically backed up by the details in each test-related question. Putting the Proteus application into practice might also be an elective to advance students' 21st-century skills. Anyway, this question sort of examines one kind of media. By contrasting the Proteus application's suitability with other programs used to teach Mechanical gadget building, recommendations for further research may be made.